Embryonic and larval development and early behavior in grass carp, Ctenopharyngodon idella: implications for recruitment in rivers. - Amy E George; Duane C Chapman (PLoS ONE, 2015)
With recent findings of grass carp Ctenopharyngodon idella in tributaries of the Great Lakes, information on developmental rate and larval behavior is critical to efforts to assess the potential for establishment within the tributaries of that region. In laboratory experiments, grass carp were spawned and eggs and larvae reared at two temperature treatments, one "cold" and one "warm", and tracked for developmental rate, egg size, and behavior. Developmental rate was quantified using Yi's (1988) developmental stages and the cumulative thermal units method. Grass carp had a thermal minimum of 13.5°C for embryonic stages and 13.3°C for larval stages. Egg size was related to temperature and maternal size, with the largest eggs coming from the largest females, and eggs were generally larger in warmer treatments. Young grass carp larvae exhibited upward and downward swimming interspersed with long periods of lying on the bottom. Swimming capacity increased with ontogeny, and larvae were capable of horizontal swimming and position holding with gas bladder emergence. Developmental rates, behavior, and egg attributes can be used in combination with physical parameters of a river to assess the risk that grass carp are capable of reproduction and recruitment in rivers.